The role of farming experience on the adoption of agricultural technologies: evidence from smallholder farmers in Uganda - Ainembabazi, John H.; Mugisha, J. (Informa UK Limited, 2014)
This article investigates the relationship between adoption of and experience with agriculturaltechnologies. We use both non-parametric and parametric estimations on data from rural farmers in Uganda.We find an inverted-U relationship between adoption of and experience with agricultural technologies in banana,coffee and maize. This suggests that farming experience is useful in early stages of adoption of a given technologywhen farmers are still testing its potential benefits, which later determine its retention or disadoption over time.Thus, gradual advances in technology development and continuous retraining of farmers are essential forsustainable adoption of agricultural technologies for some crops.